The Role of Multimedia in Science Education - Odcházelová, Tereza (Scientia in educatione, 2014)
Recently, there has been a significant decline in interest in natural science among all European countries. This fact clearly leads scientists in didactics and teachers of natural sciences to searching for new, more effective and more attractive learning methods and teaching approaches. The main aim of this study is to present multimedia as a suitable tool for teaching science in accordance with mostly recommended didactic methods. These “new” resources and technology make the education of natural science more attractive, increase learning motivation of the pupils, actively involve the pupils and it is an ideal mediator for linking theory and practice in educational process.